Realfood and cancer: analysis of the reliability and quality of YouTube content - Segado-Fernández, Sergio; Herrera-Peco, Iván; Jiménez-Gómez, Beatriz; Ruiz-Núñez, Carlos; Jiménez-Hidalgo, Pedro Jesús; Benítez de Gracia, Elvira; González-Rodríguez, Liliana G.; Torres-Ramírez, Cristina; Lozano-Estevan, María del Carmen (MDPI, 2023)
This study analyzes the quality and reliability of videos related to nutrition and cancer on YouTube. Study Design: An observational, retrospective, cross-sectional, time-limited study analyzing activity on the social network YouTube was proposed. Methods: The information from the videos was extracted through an API search tool, using the NodeXL software. The criteria to select the videos on YouTube were the keywords “real food”, “realfood”, and “cancer” and the hashtags #realfood and #cancer were present, videos in English and videos available on 1 December 2022. Results: The DISCERN value in the total number of videos viewed was 2.25 (±0.88) points, indicating low reliability. The videos uploaded by HRU represented only 20.8%. Videos suggesting that the use of foods defined as “real food” could cure cancer without the intervention of any other treatment accounted for 12.5%. Videos that provided external links to scientific/technical evidence verifying the information represented only 13.89% of the total number of videos. Of these videos, 70% corresponded to HRU. The DISCERN value for videos from HRU users was 3.05 (0.88), a value that reflects a good reliability of videos from these users. Conclusions: This study provides information on the content and quality of the videos that we can find on YouTube. We found videos of non-health users who do not base their content on any scientific evidence, with the danger that this entails for the population, but it also highlights that the videos published by HRU have greater reliability and quality, being better perceived by the population, so it is important to encourage healthcare professionals and health institutions to share verified information on YouTube.
Keywords: Cáncer en los medios de comunicación social; Cáncer - Aspectos nutricionales; Cáncer - Dietoterapia; Medios de comunicación social - Influencia; Divulgación científica; Detection; Health misinformation; Healthcare professionals; Public health; Social media; Cancer; Diet